Evaluation of the Pediatric Neurology Consultations Requested from the Pediatric Emergency Service: A Single-Center Experience - Çağatay Günay; Cem Paketçi; Gamze Sarıkaya Uzan; Didem Soydemir; Önder Karakaya; Duygu Elitez; Semra Hız Kurul; Uluç Yiş (Galenos Publishing House, 2022)
Objective: Pediatric neurology opinion is one of the most frequently requested consultations in emergency service practice. Symptoms and/or signs such as headache, altered consciousness, seizures, and focal neurological deficits are the most common consultation reasons. We aimed to retrospectively evaluate patients who were consulted with the pediatric neurology department in the pediatric emergency service. Method: This is a descriptive cross-sectional study in which the consultation notes of patients who presented to the pediatric emergency service and required a consultation with the pediatric neurology department between June 2016 and November 2019 were analyzed retrospectively. Results: The number of the consulted patients was 1,265. Sixteen patients left the hospital after their parents signed treatment and examination rejection form, 1,249 consultations were included. The most common reasons for consultation were seizure, routine follow-up of patients that receive home mechanical ventilator support, and headache. The rate of emergency neurological pathologies detected in brain computed tomography and magnetic resonance imaging was 1.7%. The most common electroencephalographic abnormality was focal epileptic discharges. Consultation rate requiring emergent intervention was 14.8% and status epilepticus, central nervous system infections, intracranial masses were the most common causes. Conclusion: The most common reason for consultation was seizure. The rate of consultations requiring acute intervention was low. We think that the emergency service admissions of patients that need examination and treatment in the outpatient clinic may harm the routine functioning of the emergency service. Community education for the use of the emergency room only when necessary is essential.